2021
DOI: 10.1002/hep.31757
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Acute HCV Infection and Transmission Networks in People Who Currently Inject Drugs in Catalonia: Usefulness of Dried Blood Spots

Abstract: BaCKgRoUND aND aIMS: Accurate identification of recent HCV infections is critical for tracing the extent and mechanisms of ongoing transmission. We aimed to validate dried blood spot (DBS) samples for the assessment of HCV genetic diversity and to determine epidemiological parameters including incidence, determinants of acute infection, and phylogenetic clustering in people who inject drugs (PWID). appRoaCH aND ReSUltS: HCV nonstructural protein 5B next-generation sequencing was performed from plasma and/or DB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 46 publications
(94 reference statements)
0
4
0
1
Order By: Relevance
“…To characterize the molecular epidemiology of the HCV epidemic in the prison setting in relation to the community, isolates from participants in the viremic group were sequenced and phylogenetically analyzed together with isolates circulating in the community. The latter were obtained from 291 PWID who attended four harm reduction services (HRS) in Barcelona province, caring for half of the PWID population in Catalonia from the HepC detect II study between May 2016 and February 2019 12 , 13 . The methods used, including total RNA extraction, retrotranscription, PCR amplification, Sanger sequencing, and phylogenetic and clustering analyses of the HCV NS5B region, are described in the Supplementary material S1 .…”
Section: Methodsmentioning
confidence: 99%
“…To characterize the molecular epidemiology of the HCV epidemic in the prison setting in relation to the community, isolates from participants in the viremic group were sequenced and phylogenetically analyzed together with isolates circulating in the community. The latter were obtained from 291 PWID who attended four harm reduction services (HRS) in Barcelona province, caring for half of the PWID population in Catalonia from the HepC detect II study between May 2016 and February 2019 12 , 13 . The methods used, including total RNA extraction, retrotranscription, PCR amplification, Sanger sequencing, and phylogenetic and clustering analyses of the HCV NS5B region, are described in the Supplementary material S1 .…”
Section: Methodsmentioning
confidence: 99%
“…Debido a sus hábitos de riesgo, en la población que acude a los centros de adicciones, la incidencia, la transmisión del virus y la reinfección son altas (Antuori et al, 2021;Midgard et al, 2016). Para su prevención, es importante fomentar la información y educación sanitaria a este colectivo, a través de la implantación de planes y programas preventivos y de promoción de la salud orientados a reducir los riesgos y evitar nuevos contagios (Alianza para la Eliminación de las Hepatitis Víricas en España -AEHVE-, 2021; Crespo et al, 2019a).…”
Section: Discussionunclassified
“…The study findings demonstrate the comparable performance of DPS for the serological and virological markers of HCV infection to that of the conventional specimen types, albeit the LLOD for DPS was noticeably higher in the study [ 105 ]. Another study (i.e., HepCdetect II Study) deciphers the usefulness of plasma and/or DBS to characterize acute HCV infection kinetics and transmission networks in individuals who recently inject drugs in Catalonia, Spain based on next-generation sequencing (NGS) of HCV nonstructural protein (i.e., NS5B) in 220 viremic PWIDs [ 106 ]. The preliminary findings of the study support 93.3% sensitivity of the protocol to identify acute HCV infections and 95.0% specificity with well-defined controls.…”
Section: The Real-world Clinical Performance Of Current Hcv Diagnostic Algorithmsmentioning
confidence: 99%
“…The preliminary findings of the study support 93.3% sensitivity of the protocol to identify acute HCV infections and 95.0% specificity with well-defined controls. HCV diagnostic interpretations by such innovative tools can also be useful to assess the performance of targeted harm reduction programs as well as to design test-and-treat strategies and to facilitating linkage to care in this key population [ 106 ]. Another study predicted the HCV-RNA testing was more feasible than DBS and showed 97.2% sensitivity and 100% specificity for viral loads >3000 IU/mL in PWIDs in real-world settings [ 107 ].…”
Section: The Real-world Clinical Performance Of Current Hcv Diagnostic Algorithmsmentioning
confidence: 99%